Bronchial carcinoid tumor as a cause of recurrent pneumonia - Gomes,Rita (2024)
Abstract Neuroendocrine tumors (NETs) are the most common primary lung neoplasms. Clinical manifestations can be subtle, and chest radiograph usually shows non-specific findings, often leading to delayed or inaccurate diagnosis. Despite their indolent nature, NETs have metastatic potential and can cause significant morbidity. Early diagnosis is critical for optimal management, as surgical resection can be curative. The challenge is to correctly diagnose this rare entity while avoiding unnecessary testing. Patients with suspected NETs should be referred to a tertiary hospital for multidisciplinary evaluation, and bronchoscopy should not be delayed. Herein is reported the case of an adolescent with asthma who presented with nonspecific respiratory and constitutional symptoms. The persistence of symptoms and imaging alterations despite multiple treatments for recurrent pneumonia raised clinical suspicion of a more serious underlying condition, leading to the diagnosis of bronchial NET.